The Influence Of Education And Training On Teacher Competency At State Senior High School 1 Gumay Talang, Lahat Regency - Eldi Merdiyansah; Saparudin Saparudin; Melia Handayani (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this study was to determine the influence of education and training on teacher competence at SMA Negeri 1 Gumay Talang, Lahat Regency. The results showed that (1) education has a significant partial effect on teacher competence, as evidenced by the calculated t-value > t-table (5.528 > 2.045). (2) training has a significant partial effect on teacher competence, as evidenced by the calculated t-value > t-table (3.285 > 2.045). (3) education and training have a significant simultaneous effect on teacher competence at SMA Negeri 1 Gumay Talang, Lahat Regency, as evidenced by the calculated f-value > f-table (27.333 > 4.183), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).